Acute and sublethal toxicity of chlorpyrifos on developmental stages of Dattaphrynus melanostictus - M. David, R. M. Kartheek, G. P. Manjunath (Journal of Applied Pharmaceutical Science, 2018)
Organophosphate (OP) compounds are commonly used as pesticides in agriculture, in homes, offices and gardens, parasiticides in veterinary medicine, and also employed as chemical warfare agents (CWA). However, extensive application of these OPs within agricultural proximity leads to the deleterious effects on inhabiting fauna. This study was aimed to find out acute toxicity and elucidates the sub-lethal effect of commercially formulated organophosphate chlorpyrifos (CPF) on Duttaphrynus melanostictus tadpoles. In this study, the 96 h LC50 value found to be 5.9 mg/L. Tadpoles exposed to three sub-lethal concentrations (0.7, 1.1, and 1.9 mg/L) of CPF showed a significant (p < 0.05) alterations in enzymatic antioxidants like catalase, superoxide dismutase glutathione peroxidase and non-enzymatic malondialdehyde, further the anticholinesterase potential of CPF was evident in concentration-dependent trend at five days of exposure tenure. It could be therefore emphasized that the CPF poses a potential threat to D. melanostictus tadpoles under the selected concentrations and hence it is advised that care should be taken when the toxicant is used and disposed under aquatic proximity. The investigation further serves as the preliminary data in the due course of regulatory surveillance and could be of a greater help in monitoring water with suspected CPF contamination.
Keywords: Acetylcholinesterase, Amphibia, Aquatic ecosystem, Oxidative stress.